2003
DOI: 10.1074/jbc.m303007200
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Metal Ions in the Catalytic Mechanism of the Yeast RNA Triphosphatase

Abstract: The Saccharomyces cerevisiae RNA triphosphatase (Cet1) requires the presence of metal ion cofactors to catalyze its phosphohydrolase activity, the first step in the formation of the 5 -terminal cap structure of mRNAs. We have used endogenous tryptophan fluorescence studies to elucidate both the nature and the role(s) of the metal ions in the Cet1-mediated phosphohydrolase reaction. The association of Mg 2؉ , Mn 2؉ , and Co 2؉ ions with the enzyme resulted in a decrease in the intensity of the tryptophan emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…This is in agreement with the model that has been previously proposed for the S. cerevisiae RNA triphosphatase [32] in which the β strands that constitute the active site of the yeast enzyme are already positioned prior to the binding of the substrate (ATP or RNA). Our spectroscopic data indicate that the binding of the ATP substrate does not lead to significant structural modifications of the protein architecture.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the model that has been previously proposed for the S. cerevisiae RNA triphosphatase [32] in which the β strands that constitute the active site of the yeast enzyme are already positioned prior to the binding of the substrate (ATP or RNA). Our spectroscopic data indicate that the binding of the ATP substrate does not lead to significant structural modifications of the protein architecture.…”
Section: Discussionsupporting
confidence: 92%
“…Growing evidence suggests that the enzymatic reaction catalysed by enzymes that belong to the metal-dependent RNA triphosphatase family requires a very precise alignment between the residues in the active site of the protein, the substrate and the essential metal-ion cofactor [32]. For instance, the fact that the RNA triphosphatase activity is supported by magnesium, but not by manganese or cobalt, while the ATPase activity is activated by manganese and cobalt, highlights the delicate differences that exist between the two phosphohydrolase activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the enzyme is activated by Mg 2ϩ , Ca 2ϩ inhibits its activity by competition with Mg 2ϩ (18). An investigation of the role of metal ion on the phosphatase activity of Cet1 (30) revealed that the binding of Mn 2ϩ did not trigger a major conformational rearrangement. Instead, it presumably perturbed the alignment of the active site residues that ultimately influence substrate catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Cet1p has a single manganese ion coordinated by three glutamates at the floor of the triphosphate tunnel and sulfate with octahedral geometry (Lima et al 1999). The presence of manganese ion in the tunnel has been implicated in triphosphatase reaction (Bisaillon and Bougie 2003).…”
mentioning
confidence: 99%